The Nipple Stimulation Meningkatkan Kontraksi Uterus Pada Ibu Yang Mengalami Persalinan Kala Dua Memanjang: Evidence Based Nursing Practices - Rahmawati, Veronica Yeni; Setyowati, Setyowati; Afiyanti, Yati (PT.Mantaya Idea Batara, 2022)
Prolonged second stage of labor can occur in some mothers who experience complications during labor. One of factors that can cause prolonged second stage of labor is inadequate contractions. Evidence based nursing practice that can be applied to apply the role of nurses in increasing uterine contractions to prolonged second stage of labor cases is nipple stimulation. In the implementation of the explanation about nipple stimulation and practical of nipple stimulation. Nipple stimulation is applied to five mothers who experience prolonged second stage of labor and involved childbirth companion in implementation. Researchers as nurses who act directly provide nipple stimulation for the five patients. The results of this study were three out of five patients experienced a significant increase in uterine contractions. This method is effectively applied by increasing uterine contractions that is seen from the adaptation mothers facing labor. Also obtained short labor time. It is suggested to mothers and childbirth companion to keep doing nipple stimulation according to instructions.